2021
DOI: 10.14202/vetworld.2021.1665-1676
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization and principal component analyses of indigenous chicken breeds in Indonesia

Abstract: Background and Aim: Understanding the phenotypic characteristics of indigenous livestock breeds is essential for their utilization and conservation. This study aimed to characterize indigenous chicken breeds in Indonesia based on phenotypic traits. Materials and Methods: Data on eight qualitative and 12 quantitative traits were recorded for 250 chickens from six breeds: Black Kedu, Gaga, Merawang, Nunukan, Pelung, and Sentul. Data were analyzed using descriptive statistics and one-way analysis of variance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
2
6
1
4
Order By: Relevance
“…The present study revealed that colors of feathers of Anjian chickens are considerably diverse, ranging from black, yellow, white, gray, buff, and red to brown, consistent with studies in different countries, including Pakistan, Sri Lanka, and Indonesia (Iqbal et al, 2015;Liyanage et al, 2015;Mahmood et al, 2017;Maharani et al, 2021). The MC1R gene that codes for the black color of feathers is located on the E locus and affects the synthesis of eumelanin and brown melanin by regulating tyrosinase activity (Feng et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study revealed that colors of feathers of Anjian chickens are considerably diverse, ranging from black, yellow, white, gray, buff, and red to brown, consistent with studies in different countries, including Pakistan, Sri Lanka, and Indonesia (Iqbal et al, 2015;Liyanage et al, 2015;Mahmood et al, 2017;Maharani et al, 2021). The MC1R gene that codes for the black color of feathers is located on the E locus and affects the synthesis of eumelanin and brown melanin by regulating tyrosinase activity (Feng et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Anjian chickens mainly have pea comb and also have single comb. Pea comb is a specifical comb type of cockfighting chickens (Iqbal et al, 2015;Liyanage et al, 2015;Mahmood et al, 2017;Asmara et al, 2019a;Maharani et al, 2021). Male Pelung chickens have a single comb (Asmara et al, 2019a), which is common in chickens in other tropical countries, such as Sri Lanka (Liyanage et al, 2015) and Nigeria (Rotimi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayam Kampung sebagai contoh mempunyai beberapa variasi warna bulu, yaitu warna hitam (EE, Ee, ee + ), tipe liar (e + e + , e + e), columbian (ee), bulu putih (II, Ii) serta warna lurik (barred/BB), sedangkan warna kulit terdiri dari warna putih/kuning (IdId/Idid), hitam atau kehijauan (idid). Bentuk jengger juga mempunyai variasi yang tinggi, yaitu bentuk tunggal (pprr), kapri (P-rr) atau walnut (P-R-) (Maharani et al 2019;Maharani et al 2021). Contoh lain tentang tingginya keragaman sifat kualitatif ayam asli Indonesia adalah pengamatan pada ayam Walik asal Kabupaten Bogor dan Sumedang (Ulfah et al 2012).…”
Section: Sifat-sifat Kualitatif Dan Kuantitatif Ayam Asli Indonesiaunclassified
“…Upaya perbaikan mutu genetik ayam lokal sudah dimulai semenjak puluhan tahun yang lalu menggunakan pendekatan inventarisasi sumber daya genetik dan program seleksi menggunakan pendekatan molkuler (Kunuti et al 2021;Hata et al 2021;Maharani et al 2021). Upaya tersebut menghasilkan rumpun baru ayam kampung yang dapat dimanfaatkan sebagai ayam galur murni atau dapat juga dijadikan sebagai ayam komersial penghasil daging (Hasnelly et al 2017).…”
unclassified